Exploring the Feasibility and Effects of a Ketogenic Diet in Patients With CNS Malignancies: A Retrospective Case Series - Panhans, Cristina M.; Gresham, Gillian; Amaral, L. J.; Hu, Jethro (Frontiers in Neuroscience, 2020)
Background: Recently, the ketogenic diet has been proposed as an adjunct treatment for a range of medical conditions including weight loss, cancer, and neurodegenerative diseases. Because malignant CNS tumors are highly dependent on glucose, the use of a ketogenic diet as an adjunct therapy is currently being explored. Controlled clinical evidence is lacking, but further studies are merited to determine the effect of a ketogenic diet and CNS malignancies. The purpose of this case series serves to explore the potential for a ketogenic for patients with CNS malignancies. Methods: Patients diagnosed with CNS malignancies following a ketogenic diet were identified between 2015 and 2017. Malignancies included a confirmed diagnosis of glioblastoma, astrocytoma, or oligodendroglioma. With guidance from a registered dietitian, ketone, glucose, and weight were regularly collected for several patients along with patient reported symptoms and side effects. Interested patients were recommended to follow a 3:1 ketogenic diet for 120 days. The ketogenic diet is a high-fat, moderate protein, and very low carbohydrate diet, where patients limited carbohydrate intake to <20 grams per day. Brain imaging was reviewed. A series of descriptive analyses were conducted. Results: The ketogenic diet was initiated in 12 patients of which 8 patients contributed data on their blood glucose and ketone levels. The majority of patients were male (n=10) with a median age of 45 (range 32-62). Diagnoses included glioblastoma (n=6), grade II/III astrocytomas (n=5) and one patient with a grade 2 spinal cord astrocytoma. The majority of patients were receiving concurrent standard treatment. All evaluable patients (n=8) maintained ketone levels above 0.5mM at 120 days from diet initiation, which generally increased from baseline. Overall, patients reported improved symptoms over the course of the diet. Imaging also suggested improved disease control and reduction in vasogenic edema. Conclusion: Taking advantage of a tumor’s metabolic rigidity can have a positive impact on patients, particularly with CNS malignancies. More structured and statistically planned clinical trials are needed to determine the margin of impact of a ketogenic diet.